How can we make sense of leadership in the 21st century - Higgs, Malcolm (Leadership & organization development journal, 2003)
Explores the development of thinking on leadership and places it in the context of the dominant discourses of the period in which studies were conducted. Argues that if a sense making paradigm is adopted. it becomes feasible to identify a model of leadership, which is relevant to the context of complexity and change facing organisations in the early twentyfirst century. The model emerges when the measure of effectiveness is changed from organisational success to the impact of the leader on followers and on building of capability. The argument for such a shift is underpinned by the movement of dominant organisational logic from a Weberian rationalanalytical one to a logic which acknowledges emotional considerations. Within the leadership arena it has been proposed that emotional intelligence is a major factor underpinning success. Presents data from recent research, which empirically demonstrates linkages between emotional intelligence and leadership. These findings are examined in conjunction with the Emergent model.